A model for the cognitive assessment of physicians - Del Bene, Victor A.; Howard, George; Geldmacher, David S.; Turnipseed, Elizabeth; Brown, Catherine; Lowry, Kathleen; Starling, Trevor; Bryan, Kate; Fry, T. Charles; Jones, Keith A.; Lazar, Ronald M. (Frontiers in Public Health, 2025)
IntroductionWith aging in the larger population and physician workforce, there has been growing emphasis on physician cognitive impairment. We propose that the determination of cognitive status in physicians, regardless of the cause, should be based on a comparison to other physicians, rather than against the non-physician populations. Our objective was to develop a normative database of healthy physicians that can be used in physician competency evaluations.MethodsThis study was a prospective cross-sectional observation design. Cognitive test data from 190 healthy physicians between the ages of 35 and 65 without work-related concerns was collected in an academic medical center neuropsychology clinic. Our primary outcome was performance on a neuropsychological test battery. All performances were z-score transformed (Mean = 0, SD = 1).ResultsWhen comparing the distribution of our physician sample to the average performance of non-physician 45-year-olds, the average physician performance is skewed to the right, indicating group-level physician performances of 0.5 to 1.0 standard deviations higher than the general population. For overall cognitive performance, multivariate regression revealed older age (−0.18, 95%CI −0.24 −0.13, p < 0.0001) was associated with lower overall cognitive performance, but still better than the average 45-year-old, non-physician group.DiscussionIn conclusion, physicians outperformed the general public on tests of cognitive functioning. Even older physicians (ages 60–65) performed above the average general population 45-year-old, reflecting preserved cognitive abilities. Existing age-corrected methods from the general population can potentially mask cognitive impairment in medical professionals.